Laparoscopic Vessel Endometriosis Resection Surgery: A Case Report and Review of Literature - Shadi Rezai; Richard A. Giovane; Tiffanie Mann; Ninad M. Patil; Elise Bardawil; Cassandra E. Henderson; Xiaoming Guan (Hindawi Limited, 2019)
Background. Endometriosis usually occurs in the pelvis and often involves the ovaries, the uterosacral and broad ligaments, and the pelvic peritoneum. In rare instances, it can occur in the vasculature of the pelvis. Patients with endometriosis present with abnormal pain, menstrual cycle disruption and infertility. Management of endometriosis is usually surgical with excision of the tissue via laparoscopic means. Case. A 42-year-old Gravida 5, Para 2-0-3-2 patient with a 22 year history of endometriosis, who had had multiple laparoscopic endometriosis resections, total abdominal hysterectomy, and an exploratory laparotomy with bilateral salpingo-oophorectomy, presented with left pelvic pain when standing, dyspareunia, and a 3.7 cm cyst on ultrasound. The patient underwent laparoscopic vessel endometriosis resection and excision of endometriotic nodules from external iliac vessels. Final pathology report showed evidence of old endometriosis in all locations. On interval follow-up, the patient reported sustained relief from pain. Conclusion. Complete resection of endometriosis from large vessels can be successfully achieved laparoscopically by a well-experienced surgeon with delicate, proper techniques.